Childhood Abuse, Social Support, and Long-Term Pharmacological Treatment Outcomes in Patients With Depressive Disorders - Lee, Ju-Yeon; Stewart, Robert; Kang, Hee-Ju; Kim, Ju-Wan; Jhon, Min; Kim, Sung-Wan; Shin, Il-Seon; Kim, Jae-Min (Frontiers in Psychiatry, 2022)
Objectives This study was performed to investigate the roles of childhood abuse and social support in predicting short- and long-term pharmacological treatment outcomes in outpatients with depressive disorders in a naturalistic 1-year prospective design. Methods Patients were recruited at a university hospital in South Korea between March 2012 and April 2017. Subjects with stepwise pharmacotherapy (switching, augmentation, combination, and mixture of these approaches) included 1246 patients at 12-week points in the acute treatment response and 1,015 patients at 12-months in the long-term treatment response. Remission was defined as Hamilton Depression Rating Scale score ≤ 7. Exposure to three types of childhood abuse (physical, emotional, and sexual) before the age of 16 and perceived social support were assessed at baseline. Results Individual associations of childhood abuse were associated with poorer treatment outcomes in the 12-month long-term phase, and no significant individual associations were found for social support level with any period outcome. In combination, any child abuse, emotional abuse, and physical abuse were significantly associated with long-term 12-month remission rate in the presence of higher level of social support after adjustment with significant interaction terms. However, no significant interactions were found with sexual abuse. Conclusion Synergistic interactive effects of child abuse and social support levels on treatment outcomes in depressive patients were found during long-term pharmacotherapy. Thus, depressed patients with a history of childhood abuse may require specialized clinical approaches, including social support, to enhance the long-term treatment outcomes.